A Concept: Enhancing Biology Learning Quality by Using Process Image - Firdha Yusmar; Devin Susbandya; Eva Laila Widita; Lailiyah Maghfiroh; Jekti Prihatin; Sutarto Sutarto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Biology learning cannot be separated from visual activities which a part of process skill approach. Visual activities involve process and supported by images. Meanwhile, the images are something that can depute real objects and have the same character of colours and shape as the original. The process is a series activities which take place gradually and continuously to achieve a goal. As for 'process image' is the series of pictures which visualise a phenomenon or a natural fact, so that students can understand the concepts and theories of biology that deals with the pictures. This paper aimed to describe the role of 'process image' to enhance High Order Thinking Skills (HOTS), retentions, process skills and learning achievements. The method of this research was analysed from some international journals about the effectiveness of process pictures in the Biology learning. Media of process image has many advantages in a visualisation of abstract concepts in the biology learning.